2012
DOI: 10.1111/j.1526-4610.2012.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Group‐Based Acceptance and Commitment Additive Therapy on Rehabilitation of Female Outpatients With Chronic Headache: Preliminary Findings Reducing 3 Dimensions of Headache Impact

Abstract: Objective.— Examine whether acceptance and commitment additive therapy is effective in reducing the experience of sensory pain, disability, and affective distress because of chronic headache in a sample of outpatient Iranian females. Background.— Chronic headaches have a striking impact on sufferers in terms of pain, disability, and affective distress. Although several Acceptance and Commitment Therapy outcome studies for chronic pain have been conducted, their findings cannot be completely generalized to chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 59 publications
2
64
0
Order By: Relevance
“…86 There are also two small RCTs of ACT for headache. 16,65 In general the controlled trials described here are small and preliminary, and of course the uncontrolled trials are susceptible to biases.…”
Section: Psychological Flexibility Clarifies and Empowers Other Existmentioning
confidence: 99%
“…86 There are also two small RCTs of ACT for headache. 16,65 In general the controlled trials described here are small and preliminary, and of course the uncontrolled trials are susceptible to biases.…”
Section: Psychological Flexibility Clarifies and Empowers Other Existmentioning
confidence: 99%
“…A recent treatment trial of patients with chronic headache found that an 8-session ACT group intervention resulted in significantly decreased disability and distress compared to treatment as usual (26). Importantly, even when presented as a brief intervention, ACT has resulted in positive long-term outcomes in patients with diabetes, pain, obesity, seizures, and psychosis (27) (28) (2931).…”
Section: Introductionmentioning
confidence: 99%
“…One small trial among individuals with CDH (CM or CTTH) has shown promise for acceptance and commitment therapy (ACT) in reducing headache-related disability and affective symptoms compared with treatment-as-usual [78].…”
Section: Emerging Treatmentsmentioning
confidence: 99%